2013
DOI: 10.1074/jbc.m112.435495
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Isocitrate Dehydrogenase Mutations to Produce 2-Hydroxyglutarate Depends on Allele Specificity and Subcellular Compartmentalization

Abstract: Background: Isocitrate dehydrogenase (IDH) 1 and IDH2 mutations can lead to 2-hydroxyglutarate (2HG) accumulation in cancer. Results: 2HG production from IDH mutants varies with subcellular localization and dependence on substrate production from the persistent wild-type IDH allele. Conclusion: IDH1 but not IDH2 mutants require a wild-type IDH partner for 2HG production. Significance: Differential 2HG production may explain the prognosis of IDH1/2 mutant cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
143
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(166 citation statements)
references
References 47 publications
22
143
1
Order By: Relevance
“…Previous in vitro studies have shown that overexpression of IDH2R140Q and IDH2R172K in cell lines resulted in different levels of 2HG production, with IDH2R172K being more efficient than IDH2R140Q. This work also showed that the subcellular localization of the mutant enzyme can affect 2HG production, because relocalization of mutant IDH1 from the cytosol to the mitochondria dramatically increased 2HG production (28). However, studying the quantitative effects of IDH mutant proteins using overexpression systems has drawbacks, because 2HG production is influenced by the level of protein expression, which is often not physiological in these model systems.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Previous in vitro studies have shown that overexpression of IDH2R140Q and IDH2R172K in cell lines resulted in different levels of 2HG production, with IDH2R172K being more efficient than IDH2R140Q. This work also showed that the subcellular localization of the mutant enzyme can affect 2HG production, because relocalization of mutant IDH1 from the cytosol to the mitochondria dramatically increased 2HG production (28). However, studying the quantitative effects of IDH mutant proteins using overexpression systems has drawbacks, because 2HG production is influenced by the level of protein expression, which is often not physiological in these model systems.…”
Section: Discussionsupporting
confidence: 52%
“…This effect has been observed in previous in vitro work where 2HG production by overexpressed (each KI was compared with WT) were performed, and *P < 0.05, **P < 0.01, and ***P < 0.001. IDH1R132H depended on the expression level of both WT and mutant proteins (28). Given this biological complexity, more accurate in vivo models should be more informative in determining the critical differences in the effects of specific IDH mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exclusivity is highly interesting, but the reason is currently not clear. Studies by others have shown that mutations differ quantitatively in 2-HG production 33,46 ; this raises the possibility that different tumor types may favor certain ranges of 2-HG concentrations. In previous studies, 33 R172 is frequently the only mutation detected, 47 again suggesting biological differences.…”
Section: R140mentioning
confidence: 99%
“…However, it is only the concentration and not the production of (R)‐2HG which is nonphysiological in IDH ‐mutated tumors, as it is also produced as a minor product by αKG reductase enzymes and is oxidized back to αKG by 2HG dehydrogenases 102. Interestingly, cells expressing mutant IDH1 produce less (R)‐2HG than those with IDH2 mutations 103. Moreover, (R)‐2HG expression by mutant IDH1 is enhanced by the co‐expression of wild‐type IDH1, leading to the formation of heterodimers 100, 103.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%